The Effect Of Moral Reasoning, Socioeconomic Status And Education Level on The Ethical Perception of Accounting Students With Love Of Money as an Intervening Variable: Pengaruh Moral Reasoning, Status Sosial Ekonomi dan Tingkat Pendidikan Terhadap Persepsi Etis Mahasiswa Akuntansi dengan Love Of Money Sebagai Variabel Intervening - Putri, Pungky Maulidiyah; Dewi, Santi Rahma (Indonesian Journal of Education Methods Development, 2022)
This study aims to determine the effect of moral reasoning, socioeconomic status and level of education on ethical perceptions of accounting students, whether love of money is able to mediate moral reasoning, socioeconomic status and education level on ethical perceptions of accounting students. This research uses quantitative, data collection is done by distributing questionnaires. The population in this study were students of the 2018 accounting study program. The sampling technique used in this study was using the Slovin formula as many as 155 respondents. The data analysis technique used is the PLS-SEM analysis technique with the SmartPLS V.3 program. The results show that (1) There is a significant influence of Moral Reasoning on the ethical perceptions of accounting students, (2) Socio-Economic Status has a significant effect on the ethical perceptions of accounting students. , (3) Education level has a significant effect on ethical perceptions of accounting students, (4) Moral Reasoning has a significant effect on Love of money, (5) Socio-economic status has a significant effect on Love of money, (6) Education level has a significant effect on Love of money , (7) Moral Reasoning, Socio-Economic Status and Education Level on Students' Ethical Perceptions”. In the test, the results obtained stating that the hypothesis can be accepted and proven, (8) Love of money is able to mediate moral reasoning on ethical perceptions of accounting students, (9) Love of money is able to mediate socioeconomic status on ethical perceptions of accounting students, (10) Love of money is able to mediate the level of education on the ethical perception of accounting students.